Cardiac MRI and Echocardiography for Early Diagnosis of Cardiomyopathy Among Boys With Duchenne Muscular Dystrophy: A Cross-Sectional Study - Prakash, Nidhi; Suthar, Renu; Sihag, Bhupendra Kumar; Debi, Uma; Kumar, Rohit Manoj; Sankhyan, Naveen (Frontiers in Pediatrics, 2022)
Background Cardiomyopathy is an important cause of morbidity and mortality in boys with Duchenne muscular dystrophy (DMD). Early diagnosis is a prerequisite for timely institution of cardioprotective therapies. Objective We compared cardiac MRI (CMRI) with transthoracic echocardiography (TTE) including tissue Doppler imaging (TDI) and speckle tracking echocardiography (STE) for diagnosis of cardiomyopathy in early ambulatory boys with DMD. Methodology This cross-sectional study was conducted between June 2018 and December 2020. Consecutive boys between 7 and 15 years of age with DMD were enrolled. Percentage ejection fraction (EF), fractional shortening, wall motion abnormalities, early diastolic mitral annulus velocity (Ea), medial mitral annulus ratio (E/Ea), and global strain were measured with STE. CMRI-derived EF, segmental hypokinesia, and late gadolinium enhancement (LGE) were studied and compared. Results A total of 38 ambulatory boys with DMD were enrolled. The mean age was 8.8 ± 1.6 years, and none had clinical features suggestive of cardiac dysfunction. In the TTE, EF was ≤55% in 5 (15%), FS was ≤28% in 3 (9%), and one each had left ventricular wall thinning and wall hypokinesia. In TDI, none had diastolic dysfunction, and STE showed reduced global strain of < 18% in 3 (9%) boys. CMRI-derived EF was ≤55% in 20 (53%) boys and CMRI showed the presence of left ventricular wall hypokinesia in 9 (24%) and LGE in 4 (11%) boys. Conclusion Cardiomyopathy remains clinically asymptomatic among early ambulatory boys with DMD. A significantly higher percentage of boys revealed early features of DMD-related cardiomyopathy in CMRI in comparison with echocardiography.